Rapamycin up-regulates triglycerides in hepatocytes by down-regulating Prox1. Issue 1 (December 2016) - Kwon, Sora; Jeon, Ji-Sook; Kim, Su; Hong, Young-Kwon; Ahn, Curie; Sung, Jung-Suk; Choi, Inho
Abstract Background Although the prolonged use of rapamycin may cause unwanted side effects such as hyperlipidemia, the underlying mechanism remains unknown. Prox1 is a transcription factor responsible for the development of several tissues including lymphatics and liver. There is growing evidences that Prox1 participates in metabolism in addition to embryogenesis. However, whether Prox1 is directly related to lipid metabolism is currently unknown. Methods HepG2 human hepatoma cells were treated with rapamycin and total lipids were analyzed by thin layer chromatography. The effect of rapamycin on the expression of Prox1 was determined by western blotting. To investigate the role of Prox1 in triglycerides regulation, siRNA and overexpression system were employed. Rapamycin was injected into mice for 2 weeks and total lipids and proteins in liver were measured by thin layer chromatography and western blot analysis, respectively. Results Rapamycin up-regulated the amount of triglyceride and down-regulated the expression of Prox1 in HepG2 cells by reducing protein half-life but did not affect its transcript. The loss-of-function of Prox1 was coincident with the increase of triglycerides in HepG2 cells treated with rapamycin. The up-regulation of triglycerides by rapamycin in HepG2 cells reverted to normal levels by the compensation of Prox1 using the overexpression system. Rapamycin also down-regulated Prox1 expression but increased triglycerides in mouse liver. Conclusion This study suggests that rapamycin can increase the amount of triglycerides by down-regulating Prox1 expression in hepatocytes, which means that the mammalian target of rapamycin (mTOR) signaling is important for the regulation of triglycerides by maintaining Prox1 expression.